Public attitudes towards the use of primary care patient record data in medical research without consent: a qualitative study. Issue 1 (10th February 2004) - Robling, M R; Hood, K; Houston, H; Pill, R; Fay, J; Evans, H M
Abstract : Objectives: Recent legislative changes within the United Kingdom have stimulated professional debate about access to patient data within research. However, there is currently little awareness of public views about such research. The authors sought to explore attitudes of the public, and their lay representatives, towards the use of primary care medical record data for research when patient consent was not being sought. Methods: 49 members of the public and four non-medical members of local community health councils in South Wales, UK gave their views on the value and acceptability of three current research scenarios, each describing access to data without patient consent. Results: Among focus group participants, awareness of research in primary care was low, and the appropriateness of general practitioners as researchers was questioned. There was general support for research but also concerns expressed about data collection without consent. These included lack of respect and patient control over the process. Unauthorised access to data by external agencies was a common fear. Current data collection practices, including population based disease registers elicited much anxiety. The key informants were equally critical of the scenarios and generally less accepting. Conclusions: This exploratory study has highlighted a number of areas of public concern when medical records are accessed for research without patient consent. Public acceptability regarding the use of medical records in research cannot simply be assumed. Further work is required to determine how widespread such views are and to inform those advising on confidentiality issues.